Simple chromatographic and spectrophotometric determination of sofosbuvir in pure and tablet forms - Abdel-Gawad, Sherif Abdel-Naby (European Journal of Chemistry, 2016)
Two methods, a reversed phase high-performance liquid chromatographic (RP-HPLC) method and a direct ultra-violet spectrophotometric method, were adopted and validated for the quantification of sofosbuvir, which is a new antiviral agent used for treatment of patients with hepatitis C virus (HCV). Validation parameters such as linearity, accuracy, precision, specificity, limits of detection and quantification were determined according to the guidelines of International Conference on Harmonization (ICH)-Q2B. The RP-HPLC method was applied on HypersilTM ODS C18 column (150×4.6 mm, 5 µm) as a stationary phase. The mobile phase was optimized according to the polarity of the studied drug. It was methanol: acetonitrile (90:10, v:v), pumped using an isocratic mode with flow rate of 1 mL/min and UV detection at 260 nm. The UV spectrophotometric method was performed for the studied drug at 260 nm. The calibration curves were linear in the ranges of 2-60 µg/mL and 5-40 µg/mL for the RP-HPLC and UV spectrophotometric methods, respectively. The proposed methods are accurate, sensitive and precise, so they can be successfully adopted for the reliable determination of sofosbuvir content in its tablet form.